New representation of the non-symmetric homogeneous bounded domains in ℂ4 and ℂ5 - Gr. Tsagas; G. Dimou (International Journal of Mathematics and Mathematical Sciences)
This paper deals with the corresponding solvable Lie algebra to each of non-symmetric homogeneous bounded domains in ℂ4 and ℂ5 by special set of matrices. Some interesting properties of Kähler manifolds are found. The theory of s-structure on a complete Riemann manifold is also studied.